2017
DOI: 10.1049/iet-nbt.2017.0009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antibacterial effect of azlocillin in conjugation with silver nanoparticles against Pseudomonas aeruginosa

Abstract: In recent years, the problems associated with bacterial resistance to antibiotics caused nanodrugs to be considered as a new way for infectious diseases treatment. The main purpose of this study was to develop a new agent against a very difficult bacterium to treat, based on azlocillin antibiotic and silver nanoparticles (AgNPs). Azlocillin was conjugated with AgNPs by chemical methods and its antimicrobial activity was studied against. using well diffusion agar method. Then, minimum inhibitory concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The capacity to combat bacterial infections in vivo was probed in research using azlocillin in conjugation with AgNPs against P. aeruginosa. Along with evidencing the enhanced antibacterial effect of the antibiotic − AgNPs, this study demonstrated that azlocillin − AgNPs conjugate was able to reduce the colonization of P. aeruginosa in the spleen of mouse models [69]. Similarly, Ipe et al [70] carried out a more complex study in which, in addition to evaluating the combined bactericidal capacity of antibiotics and AgNPs, they evaluated their cytotoxicity to establish biocompatible doses with human fibroblasts.…”
Section: Agnps As An Alternative To Combat Human Pathogenic Bacteriamentioning
confidence: 83%
“…The capacity to combat bacterial infections in vivo was probed in research using azlocillin in conjugation with AgNPs against P. aeruginosa. Along with evidencing the enhanced antibacterial effect of the antibiotic − AgNPs, this study demonstrated that azlocillin − AgNPs conjugate was able to reduce the colonization of P. aeruginosa in the spleen of mouse models [69]. Similarly, Ipe et al [70] carried out a more complex study in which, in addition to evaluating the combined bactericidal capacity of antibiotics and AgNPs, they evaluated their cytotoxicity to establish biocompatible doses with human fibroblasts.…”
Section: Agnps As An Alternative To Combat Human Pathogenic Bacteriamentioning
confidence: 83%
“…The presence of the ionic silver was also shown to enhance antibacterial properties of hydrogen peroxide against P. aeruginosa biofilms [75]. Chemically conjugated antibiotics with AgNPs enhanced the antibacterial effect of the antibiotics [76,77]. In our study, the increased sensitivity of P. aeruginosa to tobramycin, when applied in combination with Ag(PiCO)-red and Ag(BTCO), provides a potential for preventative and therapeutic treatment against P. aeruginosa biofilm infections.…”
Section: Resultsmentioning
confidence: 61%
“…However, there are a few theories that explain why SNPs are antibacterial: (A) the release of Ag + ions from SNPs denaturizes proteins by interacting with sulfhydryl groups; (B) the adhesion of SNPs to bacteria and the subsequent damage to bacteria's capacity to live; (C) the attachment of SNPs to bacteria and the subsequent damage to bacteria's ability to survive (this results in high Ag + concentrations near the bacterial cell wall over time, inhibiting bacterial growth). However, a recent study has found that Ag + generated by SNPs may be antibacterial, resulting in cell damage or repercussions [47,48]. Positive silver ions interact with the negative cell membrane, causing morphological damage to the cell and subsequent cell leakage, which leads to cell death [49].…”
Section: Discussionmentioning
confidence: 99%